Inhibition of primary breast tumor growth and metastasis using a neuropilin-1 transmembrane domain interfering peptide - Arpel, Alexia (Oncotarget, 2016)
The transmembrane domains (TMD) in membrane receptors play a key role in cell signaling. As previously shown by us a peptide targeting the TMD of neuropilin-1 (MTP-NRP1), blocks cell proliferation, cell migration and angiogenesis in vitro, and decreases glioblastoma growth in vivo. We now explored the clinical potential of MTP-NRP1 on breast cancer models and demonstrate that MTP-NRP1 blocks proliferation of several breast cancer lines including the MDA-MB-231, a triple negative human breast cancer cell line. In models with long term in vivo administration of the peptide, MTP-NRP1 not only reduced tumor volume but also decreased number and size of breast cancer metastases. Strikingly, treating mice before tumors developed protected from metastasis establishment/formation. Overall, our results report that targeting the TMD of NRP1 in breast cancer is a potent new strategy to fight against breast cancer and related metastasis.